PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN DENGAN OPINI AUDIT SEBAGAI PEMODERASI - Surya saputra, Komang Wahyu; Ramantha, I Wayan (E-Jurnal Akuntansi, 2017)
One important aspect of the financial statements is timeliness. Financial reports presented on a timely basis can reduce the occurrence of information asymmetry, then will reduce the impact of the conflict of interest between agents and principals. This is because the financial statements are information that becomes the principal consideration in decision making. Based on the theory and the results of previous research, several factors that can affect the timeliness of financial statement submission is profitability and firm size. However, both of these factors may not affect the timeliness of the delivery of financial statements due to contingency factors, so a moderator is needed to reconcile the conflicting results, ie, an audit opinion. Therefore, this study aims to determine the effect of profitability and firm size on the timeliness of financial reporting with audit opinion as a moderator variable. This research was conducted on manufacturing companies in 2012-2015 in the Indonesia Stock Exchange. Samples taken as many as 88 manufacturing companies, determined by purposive sampling method. Data was collected using non-participant observation. Analysis technique used is the Logistic Regression Analysis by using Moderated Regression Analysis. Based on the analysis concluded that profitability has no effect on the timeliness of financial reporting, firm size have a positive effect on the timeliness of financial reporting, audit opinion is able to moderate the influence of profitability on the timeliness of financial reporting, and audit opinion is not able to moderate the influence of firm size on the timeliness of financial reporting.